Serum-Free Medium for Recombinant Protein Expression in Chinese Hamster Ovary Cells - Li, Weifeng; Fan, Zhenlin; Lin, Yan; Wang, Tian-Yun (Frontiers in Bioengineering and Biotechnology, 2021)
At present, nearly 70% of recombinant therapeutic proteins (RTPs) are produced by Chinese hamster ovary (CHO) cells, and serum-free medium (SFM) is necessary for their culture to produce RTPs. In this review, the history and key components of SFM are first summarized, and its preparation and experimental design are described. Some small molecule compound additives can improve the yield and quality of RTP. The function and possible mechanisms of these additives are also reviewed here. Finally, the future perspectives of SFM use with CHO cells for RTP production are discussed.